The Effect of the Use of Audio Visual Media on Student Learning Interest in the Concept of the Pythagorean Theorem - Agnes Lugfi Wulandari mtk; Grace Netty Mainolo; Subhanudin Subhanudin; A Rasul (Lembaga Intelektual Muda (LIM) Maluku, 2023)
This study aims to determine whether there is an effect of using audio visual media on student interest in the subject matter of the Pythagorean Theorem in Class VIII of Timika Adventist Junior High School and how the effect is. The population in this study were all students of class VIII SMP Advent Timika with a total of 124 students. The results of the t-test statistic test using the Independent Sample Test technique to test the hypothesis